Supervisi Akademik Kepala Sekolah terhadap Manajemen Pembelajaran PAUD - Ittihad Ittihad (PALAPA, 2019)
Academic supervision is inseparable from the teacher in conducting learning management. The purpose of this study was to obtain new findings about: 1) Conformity between learning management in Al Urwatul Usqo ECD with Permendikbud 137 of 2014; 2) Causes have not been supported by academic supervision by the Al Urwatul Usqo PAUD school principal. This research is a qualitative study with a type of research, namely a case study. This research was conducted in Al Urwatul Usqo PAUD. The subjects in this study were principals. Data collection techniques used are interviews and documents. Data analysis techniques in this study used qualitative descriptive analysis techniques. Five "Why" developed by Sakichi Toyoda in 1930 and developed based on discussions made by academic supervision by principals, namely by techniques: (1) Learning management consisting of planning, implementation and evaluation is in accordance with Permendikbud 137 of 2014; (2) Causes that are not supported by academic supervision by the principal are because the appointment of the principal is not in accordance with the competency standards of the KB / TK principals needed in Permendikbud 137 of 2014. Suggestions that can be given are: (1) for Al Urwatul Usqo PAUD managers if want to be appointed headmaster needs to look at the competency standards of KB / TK principals needed in Permendikbud 137 of 2014; (2) Principals can improve the competency of principals by studying or studying undergraduate education at PAUD so that it can facilitate the function of the wrong headmaster, only academic supervision.